Convergence of mobile and stationary next-generation networks - Iniewski, Krzysztof (Hoboken, N.J. : John Wiley & Sons, 2010)
'Filled with illustrations and practical examples from industry, this book provides a brief but comprehensive introduction to the next-generation wireless networks that will soon replace more traditional wired technologies. Written by a mixture of top industrial experts and key academic professors, it is the only book available that covers both wireless networks (such as wireless local area and personal area networks) and optical networks (such as long-haul and metropolitan networks) in one volume. It gives engineers and engineering students the necessary knowledge to meet challenges of next-gen network development and deployment'--
'This book covers wireless networks such as wireless local area networks (WLAN), wireless personal area networks (WPAN), wireless access, 3G/4G cellular, and RF transmission, as well as optical networks like long-haul and metropolitan networks, optical fiber, photonic devices, VLSI chips'--
Includes bibliographical references and index.
Keywords: Wireless LANs; Optical fiber communication; Internetworking (Telecommunication)